Nurse-caregiver communication of hospital-to-home transition information at a tertiary pediatric hospital in Western Australia: A multi-stage qualitative descriptive study - Zhou, Jo; Roberts, Pamela; Della, Phill (ELSEVIER SCIENCE INC, 2021)
Purpose: To observe and describe nurse-caregiver communication of hospital-to-home transition information at the time of discharge at a tertiary children's hospital of Western Australia. Design and methods: A multi-stage qualitative descriptive design involved 31 direct clinical observations of hospital-to-home transition experiences, and semi-structured interviews with 20 caregivers and 12 nurses post-discharge. Eleven caregivers were re-interviewed 2–4 weeks post-discharge. Transcripts of audio recordings and field notes were analyzed using content analysis. Medical records were examined to determine patients' usage of hospital services within 30 days of discharge. Results: Four themes emerged from the content analysis: structure of hospital-to-home transition information; transition information delivery; readiness for discharge; and recovery experience post-hospital discharge. Examination of medical records found seven patients presented to the Emergency Department within 2–19 days post-discharge, of which three were readmitted. Primary caregivers of three readmitted patients all had limited English proficiency. Conclusion: The study affirmed the complexity of transitioning pediatric patients from hospital to home. Inconsistent content and delivery of information impacted caregivers' perception of readiness for discharge and the recovery experience. Practice implications: Nurses need to assess readiness for discharge to identify individual needs using a validated tool. Inclusion of education on hospital-to-home transition information and discharge planning/process is required in the orientation program for junior and casual staff to ensure consistency of information delivery. Interpreter services should be arranged for caregivers with limited language proficiency throughout the hospital stay especially when transition information is being provided. Nurses should apply teach-back techniques to improve caregivers' comprehension of information.